Screening of Soybean Varieties against Salinity stress at an Early Vegetative Growth Stage under Hydroponic Conditions - Fauziah, Annisa; Prameswari, Wuri; Inoriah, Entang (Indonesian Journal of Agricultural Research, 2024)
Salinity is a principal environmental severe stress that significantly threatens crop production, including soybeans. It considerably affects various plant growth and physiological traits at different soybean growth stages, especially in coastal areas. However, the high soil pH in these regions presents a challenge. In this study, we screened two soybean varieties using an easy and rapid, and inexpensive screening technique. This study aimed to select soybean tolerance salinity stress in the early vegetative growth stage under hydroponic culture. The study was meticulously done with a randomized complete block design comprising two factors (varieties and NaCl) with three replications. Two soybean varieties, i.e., ‘Gepak Kuning and Dering 1’, were tested at three NaCl levels, i.e., 0, 60, and 120 mM. The results showed that each type of plant behaved differently to each stress level. The stress of 60 mM revealed that the Dering 1 variety was tolerant, whereas the Gepak Kuning variety was only somewhat tolerant. In conclusion, the Gepak Kuning variety was tolerant to 60 mM salinity stress, while the Dering 1 variety showed 60 mM and 120 mM salinity tolerance. These results will help select the most tolerant varieties to develop salinity-tolerant varieties in the future.